4 HIGH-PROTEIN, HIGH-CALORIE ICE-CREAM PRESCRIPTION IN AN ORTHOGERIATRIC INPATIENT POPULATION. (25th October 2022) - Cloney, T; Crowley, P; Lynch, K; Gannon, E; McGurk, C; Coakley, K; Ahern, E
Abstract: Background: At a major trauma centre in the South of Ireland, all older adults admitted with hip and other fragility fractures are co-managed by the Orthopaedic & Orthogeriatric services with an average of over 500 hip fractures a year. A recent publication by described improving calcium and protein intake by using dairy foods as a readily accessible intervention that reduces the risk of falls and fractures in aged care residents. Foods used included cheese, yoghurt and milk being described as "low cost" and "palatable". Other dairy alternatives such as ice-cream are not used as not protein or calcium rich. In Ireland high calorie-high protein ice-cream is widely available (10g protein, 220 kcal/100g serving). Methods: A point prevalence survey relating to the preference of calcium and/or protein rich food 'snacks' was completed on 20 inpatients in hospital with a hip or other fragility fracture. Survey Questions: (1) Would an additional calcium and/or protein rich food snack be acceptable to you?; (2) Which food snack would you prefer: a serving of milk, cheese, yogurt, or ice-cream?; (3) What time would you prefer to eat an additional snack? Morning, afternoon, or evening? Results: The majority of participants (95%; 19/20) replied an additional snack would be acceptable. With reference to snack preference: 35% (7/20) would prefer a serving of yoghurt, 30% (6/20) ice-cream, 25% (5/20) cheese and only 10% (2/20) would prefer milk. The majority said they would prefer to be offered a snack in the afternoon (55%; 11/20). Conclusion: Our inpatient population would benefit from the addition of such snacks to optimise recovery and bone health. Patient preference needs to inform any dietary or menu modifications. Following our survey, in addition to calcium and vitamin D supplementation, high-protein high-calorie ice-cream is offered and prescribed to patients if eating less than 50% of their energy dense meals.